Tucidinostat plus exemestane for postmenopausal patients with advanced, hormone receptor-positive breast cancer (ACE): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 6 (June 2019) - Jiang, Zefei; Li, Wei; Hu, Xichun; Zhang, Qingyuan; Sun, Tao; Cui, Shude; Wang, Shusen; Ouyang, Quchang; Yin, Yongmei; Geng, Cuizhi; Tong, Zhongsheng; Cheng, Ying; et al.
Summary: Background: Tucidinostat (formerly known as chidamide) is an oral subtype-selective histone deacetylase inhibitor. In an exploratory study, the combination of tucidinostat with exemestane showed preliminary signs of encouraging anti-tumour activity in patients with advanced hormone receptor-positive breast cancer. To build on these findings, we aimed to assess the efficacy and safety of this combination in a randomised trial in a larger population of postmenopausal patients with advanced, hormone receptor-positive breast cancer. Methods: We did the randomised, double-blind, placebo-controlled, phase 3 ACE trial at 22 specialist cancer centres in China. Eligible patients were postmenopausal women (aged ≥60 years or aged <60 years if their serum follicle-stimulating hormone and oestradiol concentrations were within postmenopausal ranges) with hormone receptor-positive, HER2-negative breast cancer, whose disease had relapsed or progressed after at least one endocrine therapy (either in advanced or metastatic or adjuvant setting), and who had at least one measurable lesion, adequate organ function, Eastern Cooperative Oncology Group (ECOG) performance status of 0–1, and adequate haematological and biochemical parameters. Endocrine therapy did not have to be the most recent therapy before randomisation, but recurrence or progression after the most recent therapy was a prerequisite. Patients were randomly assigned (2:1) by a dynamic randomisation scheme via an interactive web-response system to receive 30 mg oral tucidinostat or placebo twice weekly. All patients in both groups also received 25 mg oral exemestane daily. Randomisation was stratified according to the presence of visceral metastases (yes vs no). Patients, investigators, study site staff, and the sponsor were masked to treatment assignment. The primary endpoint was investigator-assessed progression-free survival. Efficacy analyses were done in the full analysis set population, comprising all patients who received at least one dose of any study treatment, and safety analyses were done in all patients who received at least one dose of any study treatment and for whom at least one safety case report form was available. This study is registered withClinicalTrials.gov, numberNCT02482753 . The study has reached the required number of events for final analysis of the primary endpoint. The trial is no longer enrolling patients, but follow-up for investigation of overall survival is ongoing. Findings: Between July 20, 2015, and June 26, 2017, 365 patients were enrolled and randomly assigned, 244 to the tucidinostat group and 121 to the placebo group. The median duration of follow-up was 13·9 months (IQR 9·8–17·5). Investigator-assessed median progression-free survival was 7·4 months (95% CI 5·5–9·2) in the tucidinostat group and 3·8 months (3·7–5·5) in the placebo group (HR 0·75 [95% CI 0·58–0·98]; p=0·033). The most common grade 3 or 4 adverse events in either group were neutropenia (124 [51%] of 244 patients in the tucidinostat group vs three [2%] of 121 patients in the placebo group), thrombocytopenia (67 [27%] vs three [2%]), and leucopenia (46 [19%] vs three [2%]). Serious adverse events of any cause occurred in 51 (21%) of 244 patients in the tucidinostat group and seven (6%) of 121 patients in the placebo group. No treatment-related deaths were reported. Interpretation: Tucidinostat plus exemestane improved progression-free survival compared with placebo plus exemestane in patients with advanced, hormone receptor-positive, HER2-negative breast cancer that progressed after previous endocrine therapy. Grade 3–4 haematological adverse events were more common in the tucidinostat plus exemestane group than in the placebo plus exemestane group. Tucidinostat plus exemestane could represent a new treatment option for these patients. Funding: Chipscreen Biosciences.